2019
DOI: 10.1111/jace.16269
|View full text |Cite
|
Sign up to set email alerts
|

A strategy for defects healing in 3D printed ceramic compact via cold isostatic pressing: Sintering kinetic window and microstructure evolution

Abstract: In this study, we developed a unique defect healing method for 3D printed ceramic compact via cold isostatic pressing (CIP) after debinding, and typical features of interlayer interface defects of 3D-printed zirconia compact were characterized and found to be reduced significantly. The characteristic sintering kinetics window and microstructure evolution of the healed sintered bodies were systematically investigated, which was found to be quite different from conventional shaping methods. The three sintering s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Hence, it is confirmed that it is 1250°C at which open pores disappear and the boundary of the 2nd and the 3rd sintering stage. Furthermore, interlayer defects could be healed in the following sintering stage due to the RD of 95.43% is obtained at 1300°C …”
Section: Resultsmentioning
confidence: 99%
“…Hence, it is confirmed that it is 1250°C at which open pores disappear and the boundary of the 2nd and the 3rd sintering stage. Furthermore, interlayer defects could be healed in the following sintering stage due to the RD of 95.43% is obtained at 1300°C …”
Section: Resultsmentioning
confidence: 99%
“…Sintering is a complex process and could be principally divided into three stages, that is, the initial, intermediate, and final stages of sintering 22 . Sintering activation energy of initial stage is extremely significant to understand the sintering mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…Sintering is a complex process and could be principally divided into three stages, that is, the initial, intermediate, and final stages of sintering. 22 Sintering activation energy of initial stage is extremely significant to understand the sintering mechanism. In this study, on basis of the researches of Bannister, 23 Keski and Cutler, 24 and Woolfrey and Bannister, 25 sintering activation energy of initial stage is calculated according to the linear shrinkage of initial stage.…”
Section: Sintering Densification Behaviormentioning
confidence: 99%
“…Works by Santoliquido et al [17] and Shuai et al [18] have detailed the use of DLP-stereolithography for the fabrication of Al 2 O 3 architectures with fine and complex lattice structures. However, it is worth noting that the presence of photosensitive resin in printed green parts and its removal during the debinding process can result in a large porosity in the debound parts [19], which can lengthen the pathways for substance migration at high temperatures and be an obstacle for the sintering densification [20,21]. For this reason, an increased sintering temperature is required for the debound samples to form dense ceramic parts.…”
Section: Introduction mentioning
confidence: 99%